Influence of spraying schedule on the control of horseweed plants (Conyza spp.) - Souza, Deomarques de; Côrrea, Fernando Rezende; Silva, Nelmício Furtado da; Cavalcante, Wendson Soares da Silva; Ribeiro, Daniele Ferreira; Rodrigues, Estevão (Brazilian Journal of Science, 2023)
Assuming that applications made at different times of the day, that is, morning, afternoon or night applications are usually carried out under specific environmental conditions that can positively or negatively influence the effectiveness of the herbicides. The objective of this study was to know the best time for herbicide application and whether there is a need for the use of adjuvants or not in the control of weeds in soybean crops. The treatments consisted of applications at different times of the day, with and without adjuvants, the herbicides were used in a unique combination of glyphosate + 2,4-D+ paraquat dichloride, as well as weeded and non-weeded control. The experiment was carried out at the Teaching, Research and Extension Farm of the UniBRAS Faculty – Rio Verde – GO, in a Red Distroferric Oxisol (LVDf). The experimental design used was a randomized block, with 4 replications. Droplet size, droplet number and coverage were evaluated for all treatments in different collection positions (lower, middle and upper third), phytotoxicity by weed control at 7, 14 and 21 days after application (DAA), mass 1000 grains and grain yield. Data were submitted to analysis of variance (p<0.05) and cases of significance were submitted to the Scoot-Knott mean test (p<0.05), using the SISVAR® statistical software.